Refugee protection in Central Africa : What forced migrations'governance for Central African States ? : The case of Cameroon - (:unkn) unknown (My University, 2020)
In the past decade, forced migration has been a particular and growing concern in Africa and in many parts of the world, as far as they created many complex challenges. These migrations, very often massive, unexpected, and generally caused by armed conflicts, human rights violations, violence, environmental degradation, have jeopardized the survival of many populations whose proportions reached alarming rates between 2011 and 2017, as it is stated in 2015's Global Annual Report of the UNHCR. But this already vulnerable population often remains, beyond any observation, highly precarious within some host States. The paradox of the failure of forced migrants's protection is maintained by the constancy of the consecration of their rights in international, regional and national legal instruments and the diversity of humanitarian actors at their side. Sub-Saharan Africa, which, according to the report quoted above, has around 4.41 million refugees out of a total of 21.3 million in the world, is no exception to this factual reality. In view of this dramatic and humanely burning situation in Central Africa, which has led to a significant reconfiguration of the humanitarian space due to the exponential increase of forced population displacement, fuelled by recurrent conflict inflation in the Lake Chad Basin, the Central African Republic, the Democratic Republic of Congo, and the South West and North-West Cameroon – to mention only those cases whose echo of the tragedies bear witness to the topicality of this phenomenon in this African sub-region -, and the crossborder threats that weigh within this sub-Saharan african territoriality, my thesis focuses to map the national refugee protection system of the State of Cameroon, historically well known as a welcoming and hospitable country whose geographical position is strategic in the sub-regional area of Central Africa. This exercise allows on the one hand, the analysis of normative, structural and infrastructura
Keywords: African Research